è¿ç”¨å¡ç‰‡æé«˜ SANTO FRANSISKUS ASISI é«˜ä¸ äºŒå¹´çº§æ–‡ç§‘çå¦ç”Ÿçš„è¯è¯è®¤è¯»èƒ½åŠ› - Bong, Helmi; ., Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
æ‘˜è¦ï¼šè¯æ±‡æ•™å¦æ˜¯è¯è¨€æ•™å¦åŸºç¡€ä¹‹ä¸€,å®ƒå¯¹è¯¾å ‚æ•™å¦å’Œå¦ç”Ÿè¯è¨€èƒ½åŠ›çš„åŸ¹å…»æ˜¯éžå¸¸é‡è¦çš„ã€‚è¯æ±‡æ•™å¦çš„å…¶ä¸ä¸€ä¸ªä»»åŠ¡å°±æ˜¯è¯è¯è®²è§£,å¦ç”Ÿå¦ä¹ è¯è¯å¸¸é‡åˆ°çš„éš¾ç‚¹æ˜¯å¾ˆéš¾è®¤è¯»è¯è¯çš„æ±‰å—,å› æ¤å¸¸å¸¸ä¾èµ–æ‹¼éŸ³å¸®åŠ©ä»–ä»¬è®¤è¯»,è¿™æ ·å½“ç„¶ä¼šå½±å“ä»–ä»¬çš„è®¤è¯»èƒ½åŠ›,ä¹…è€Œä¹…ä¹‹å¯¹ä»–ä»¬çš„å¦ä¹ æ•ˆçŽ‡ä¹Ÿä¼šäº§ç”Ÿä¸åˆ©å½±å“ã€‚åœ¨è¿™ç§æƒ…å†µä¸‹,ä¸ºäº†å¸®åŠ©å¦ç”Ÿæ›´å®¹æ˜“è®¤è¯»è¯è¯,ç¬”è€…åšäº†ç ”ç©¶ã€‚é¦–å…ˆç¬”è€…å¯¹SANTO FRANSISKUS ASISIé«˜ä¸äºŒå¹´çº§æ–‡ç§‘äºŒçå’Œæ–‡ç§‘ä¸‰çå¦ç”Ÿè¿›è¡Œäº†å‰æµ‹,ç„¶åŽè¿ç”¨å¡ç‰‡è¿›è¡Œäº†ä¸‰è¯¾æ—¶è¯è¯è®¤è¯»æ•™å¦ã€‚é€šè¿‡è¿™ç§æ•™å¦ä¹‹åŽ,ç¬”è€…ç»™å¦ç”Ÿè¿›è¡Œäº†åŽæµ‹ã€‚ç»è¿‡å‰æµ‹å’ŒåŽæµ‹å‘çŽ°è¿ç”¨å¡ç‰‡è¿›è¡Œæ•™å¦æœ‰æ•ˆæé«˜å¦ç”Ÿå¯¹è¯è¯è®¤è¯»èƒ½åŠ›,ä»Žè€Œå–å¾—æ›´å¥½çš„æ•™å¦æ•ˆæžœã€‚ å…³é”®è¯ï¼šè¯è¯,å¡ç‰‡,è¯è¯è®¤è¯»æ•™å¦ Abstract : Vocabulary studying is the basic study in learning language, Itâ€™s act is very important in teaching-learning process and it can help students to improve their language skill. One of the part in vocabulary studying is teaching vocabularies. In the vocabulary studying, students usually have difficulties in recognizing Hanzi (chinese characters) vocabularies, students often too focus in pinyin to help them study vocabularies, which in the future will influence their ability in recognizing the vocabularies. If it last for a long time students will dependent to pinyin, and itâ€™s not good for their chinese improvement. Further more, one to help students to recognize the vocabularies easily, the author has done one research. The first step was gave the pre-test for the second grade of social 2 and social 3 of SANTO FRANSISKUS ASISI Senior High School. The author used the vocabularies cards to teach them vocabulary studying. The next step was gave the post-test. After that, the author compared the pre-test and the post-test results. It is proved that using the vocabularies card in doing the teaching learning process can help students to improve their ability in recognizing the vocabularies. In conclusion, it gives a good effect in the teaching learning. Â Key words: Vocabularies, Vocabulary Card, Recognize Vocabularies Teaching